PENGEMBANGAN MODUL DIGITAL MATEMATIKA DENGAN MENGGUNAKAN FLIP PDF CORPORATE EDITION - Siti Khoiriyah; Ana Istiani; Rahman Cahyadi; Rahmatika Kayyis (EMTEKA: Jurnal Pendidikan Matematika, 2022)
The application of limited face-to-face learning is a new signification for the learning process after more than a year of learning activities being fully implemented online. However, the application has not been a solution for students who spend more time studying independently at home than at school. The students need effective learning media based on their needs and easy online access. Moreover, they also need an interactive learning media to make learning process effectively. This study aims to produce a digital module on the set materials. The digital module development process is carried out through the ADDIE stages, namely Analysis, Design, Development, Implementation, and Evaluation. The development resulted in a digital module on the set of materials that had gone through the validator stage from a team of experts with a result of 86.45%, it means that the product is suitable to use. In addition, the digital module has also gone through the pilot phase on students and received a very good response of 50.19%, and a good response of 26.9%. Analysis of student learning achievement shows that the use of digital modules has an impact of 84.37% of students that getting scores suffiecient with the minimum criteria of mastery learning (KKM) . Keywords: Flip Pdf Corporate Edition, Math Digital Module